2009
DOI: 10.4314/ajcem.v11i1.44092
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Characteristics Of Adults Screened For Hiv/Aids In A Rural Community In Benue State, Nigeria

Abstract: Background: Benue state has been considered among the 'hot zones' for HIV/AIDS in Nigeria with a prevalence rate of 9.3 among adults aged 15 to 45 years. Yet, there is paucity of information on the socio-demographic factors associated with this level of prevalence. We hereby report the prevalence and socio-demographic factors associated with HIV among adults in Abwa-Mbagene, Benue state, Nigeria. Methods: Adults in Abwa-Mbagene community who accepted to participate between 9th and 24th of August 2007 were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This profile generally represents what obtains in other Nigerian studies involving HIV patients (Laah and Ayiwulu, 2010;Nakama et al, 2015;Odimayo et al, 2010). Home based care studies in other parts of Africa among HIV populations have also shown a predominance of females of a younger age group than men (3, 8) and this is in keeping with reports of increased susceptibility to HIV in younger women (Ramjee, 2013;Glynn et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…This profile generally represents what obtains in other Nigerian studies involving HIV patients (Laah and Ayiwulu, 2010;Nakama et al, 2015;Odimayo et al, 2010). Home based care studies in other parts of Africa among HIV populations have also shown a predominance of females of a younger age group than men (3, 8) and this is in keeping with reports of increased susceptibility to HIV in younger women (Ramjee, 2013;Glynn et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…Although high prevalence of HIV in Benue State has often been attributed to cultural habits such as un-protected sex at night gatherings including during burial night wake keepings [13], low literacy and poverty [7]; it is not clear whether HBV which have similar mode of transmission and associated risk factors like HIV will share in these attributes.…”
Section: Discussionmentioning
confidence: 99%
“…An electronic forum, Nigerian Best Forum, has posted an exchange on this issue with one blogger citing Professor John Idoko, Director General of the National Agency for the Control of AIDS, as follows: "The National Agency for the Control of AIDS (NACA) has attributed the high HIV prevalence in Benue State to poverty, illiteracy and the lack of empowerment for women" (8). One study in a Benue community found HIV prevalence to be highest among farmers, divorcees and those with educational level at primary school and below, with the main risk factor being unprotected casual sex (9). Further analysis of Benue state and how it is currently and historically situated in the larger Nigerian polity and economy may also help shed more light on the epidemiology of HIV in Benue.…”
Section: Hiv and Art In Nigeria And Benue Statementioning
confidence: 99%